Process Synthesis And Optimisation For Multi-Biodiesel Mixture Production - Pang, Yi Wen (2020)
Nowadays, biodiesel has been widely used as an alternative of petroleum derived diesel due to its sustainable characteristic. Biodiesel is blended with diesel and used at various concentrations. Biodiesel derived from a single kind of biological resource may not be available all year long since most biological resources are seasonal, limiting the accessibility of biodiesel. The aim of this research is to synthesise and optimise the process for multi-biodiesel mixture production used in biodiesel-diesel blending. An optimisation model is proposed to investigate the diverse biodiesel utilisation strategic in biodieseldiesel blend production. Various factors affecting the diverse biodiesel utilisation strategic are considered such as biodiesel feedstocks, biodiesel production capacities, crude oil distillation capacities, costs and fuel properties criteria. Demonstration case study is discussed to evaluate the performance of the model. The case study is conducted based on different demand fulfilment percentage, they are 50.00 %, 65.00 %, 80.00 % and 95.00 %. As demand increases, total water transport cost increases. This is due to a more diverse biodiesel being used in biodiesel-diesel blending process. From the case study, diverse biodiesel utilisation strategic in biodiesel-diesel blend production at demand fulfilment of 65.00 % has the highest revenue amongst the cases at other demand fulfilment, which is RM 37072762.90 k/yr. The result shows that biodiesel availability, markets’ demand fulfilment, location of biodiesel production plants and blending facilities have great influence in performance of diverse biodiesel utilisation strategic.